2011
DOI: 10.3109/09637486.2011.640309
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of chicken feather hydrolysate as a novel fermentation substrate for production of exopolysaccharide and mycelial biomass from edible mushroomMorchella esculenta

Abstract: This study was performed to investigate the usability of chicken feather hydrolysate (Chicken feather peptone (CFP)) as substrate for mycelial biomass and extracellular polysaccharides (EPS) production from edible mushroom Morchella esculenta. The ability of CFP to support biomass and EPS production in edible mushroom M. esculenta was compared to those of two commercial peptones (Tryptone peptone (TP) and Fish peptone (FP)). The maximum biomass (16.3 g/l) and EPS (4.8 g/l) concentrations were achieved with TP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…The present hydrolysis experiments were performed using acids. However, the method used was different from those reported in previous studies , . As seen in Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The present hydrolysis experiments were performed using acids. However, the method used was different from those reported in previous studies , . As seen in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Recently, it has been reported that protein hydrolysate prepared from chicken feathers can be used as a general growth substrate for bacteria . In other studies the same protein hydrolysate was used as a substrate in fungal fermentation to produce carotenoids and polysaccharides . These studies indicated that chicken feather protein hydrolysate had high protein, mineral and amino acid contents as well as high levels of cysteine and glycine amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feathers constitute up to 100 g kg −1 of total chicken weight, and are composed of over 900 g protein per kg (Taskin et al . ). Nonetheless, despite their low cost and abundant availability, industrial applications of feathers are limited and chicken feather is usually treated as waste (Reddy ).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, inexpensive alternatives to these components are preferred as medium supplements. Annually, about 5 million tons of chicken feathers are generated by the poultry industry (Gao et al 2014), and this is used for the production of animal feed supplements such as feather meal (Taskin et al 2012) or disposed of in landfills (Stiborova et al 2016). Since 90-92% of feather is composed of keratin, a protein rich in cysteine, arginine, threonine and hydrophobic amino acids, it can have nutrient potential providing its structure can be effectively broken down.…”
mentioning
confidence: 99%